2017
DOI: 10.35790/ecl.5.2.2017.18538
|View full text |Cite
|
Sign up to set email alerts
|

250 Gambaran Benigna Prostat Hiperplasia di RSUP Prof. Dr. R. D. Kandou Manado Periode Januari 2014 – Juli 2017

Abstract: Benign prostatic hyperplasia (BPH) is defined as stromal cell proliferation of prostate gland which causes enlargement of the gland. It manifests as urine flow disturbance, difficult to urinate, and desire to urinate, however, the urine emission is low. In 2013, Indonesia has 9.2 million cases of BPH among men aged over 60 years. This study was aimed to obtain the profile of BPH cases at Prof. Dr. R. D. Kandou Hospital Manado in the period of January 2014 to June 2017. This was a retrospective descriptive stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
2
0
3
Order By: Relevance
“…The CLasP study showed that TURP was found significantly effective to relieve LUTS, improve Qmax and health-related quality of life (HRQL), decrease PVR (post-void residual), and showed comparable outcome to low power laser coagulation therapy (19). Also, several complications of BPH that are strong indications of TURP are [1] recurrent urinary retention, [2] recurrent hematuria after being swept with 5a-reductase inhibitors, [3] renal insufficiency or superior urinary tract dilatation, [4] bladder stones in the urinary tract, [5] recurrent urinary tract infections (13). This is consistent with the results of the study that the TURP indications are recurrent urinary retention (54.9%), urinary tract stones (21%), failure of medical therapy (10.5 %), hernia or hemorrhoids (8%), severe LUTS (3.7%), and renal insufficiency (1.9%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CLasP study showed that TURP was found significantly effective to relieve LUTS, improve Qmax and health-related quality of life (HRQL), decrease PVR (post-void residual), and showed comparable outcome to low power laser coagulation therapy (19). Also, several complications of BPH that are strong indications of TURP are [1] recurrent urinary retention, [2] recurrent hematuria after being swept with 5a-reductase inhibitors, [3] renal insufficiency or superior urinary tract dilatation, [4] bladder stones in the urinary tract, [5] recurrent urinary tract infections (13). This is consistent with the results of the study that the TURP indications are recurrent urinary retention (54.9%), urinary tract stones (21%), failure of medical therapy (10.5 %), hernia or hemorrhoids (8%), severe LUTS (3.7%), and renal insufficiency (1.9%).…”
Section: Discussionmentioning
confidence: 99%
“…BPH is the second most common disease found in urology clinics in Indonesia after urinary tract stones. In 2013 in Indonesia there were 9.2 million cases of BPH, mostly dominated by men aged over 60 years (2). BPH prevalence is on the rise.…”
Section: Introductionmentioning
confidence: 99%
“…Sebaliknya, pada penderita kanker prostat seringkali ditemukan kadar PSA tidak mengalami peningkatan atau kadar PSA berada dalam batas normal. 11 Hal ini disebabkan karena PSA merupakan spesifik organ bukan spesifik dalam mendeteksi keganasan. Sehingga, perlu dilakukan pemeriksaan lanjutan untuk menentukan diagnosis pasti pada kejadian kelainan prostat.…”
Section: Pendahuluanunclassified
“…(2014) dan Adelia (2017) dimana ditemukan kejadian adenokarsinoma prostat dan hiperplasia prostat jinak (BPH) paling banyak ditemukan pada rentang usia 61-70 tahun. 6,10,11 Hasil penelitian pada Tabel 3 ditemukan penderita kelainan prostat paling banyak menderita keluhan LUTS (62,5%). Hal ini sejalan dengan penelitian Sianipar dkk (2005) bahwa pasien dengan gangguan prostat paling banyak mengalami keluhan yang berkaitan dengan LUTS.…”
Section: Hasil Dan Pembahasanunclassified
See 1 more Smart Citation